2018
DOI: 10.1002/glia.23458
|View full text |Cite
|
Sign up to set email alerts
|

Microglia heterogeneity along a spatio–temporal axis: More questions than answers

Abstract: Microglia are resident macrophages of the central nervous system; they arise during early embryonic development and persist throughout adulthood. These unique cells provide developmental support, contribute to adult brain homeostasis and impart immune protection during infection. Dysregulated microglia are implicated in the pathophysiology of several neurological disorders, including Alzheimer disease, and as such, a better understanding of their regulation and function is required for rational therapeutic des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(63 citation statements)
references
References 107 publications
4
57
0
1
Order By: Relevance
“…; Li and Barres ). In addition to this range of normal behavior, studies show that microglia also differ in their phenotype across brain regions and lifespan in an extraordinarily complex fashion (Silvin and Ginhoux ). An early description of these differences by Lawson et al .…”
Section: Spatial and Temporal Diversity Of Microglial Phenotypesmentioning
confidence: 99%
“…; Li and Barres ). In addition to this range of normal behavior, studies show that microglia also differ in their phenotype across brain regions and lifespan in an extraordinarily complex fashion (Silvin and Ginhoux ). An early description of these differences by Lawson et al .…”
Section: Spatial and Temporal Diversity Of Microglial Phenotypesmentioning
confidence: 99%
“…Brain regions are often defined by the primary neuronal subtype contained within that region, as well as to which other regions these neurons connect. However, recent scRNA‐seq and proteomics studies have observed a high level of heterogeneity within individual brain regions (Tasic et al, ; Zeisel et al, ), indicating that in addition to heterogeneity between traditionally defined brain regions, there may also be significant intra‐regional heterogeneity (Ayata et al, ; Silvin & Ginhoux, ). Early flow cytometry‐based studies examining the potential for spatial heterogeneity of microglial phenotypes described marked variations of canonical microglial markers from microglia isolated from the hippocampus, spinal cord, cerebellum, cerebral cortex, and striatum of 11–12 week‐old male mice (de Haas, Boddeke, & Biber, ).…”
Section: Intrinsic Differences Between Brain Regions May Impart Sex‐smentioning
confidence: 99%
“…Microglia have traditionally been regarded as a rather homogeneous population. However, recent studies in mice have revealed population heterogeneity related to the CNS region . In addition, higher turnover rates of microglia were reported from the olfactory bulb, hippocampus, and cerebellum compared to those in the cortex, midbrain, and hypothalamus .…”
Section: Introductionmentioning
confidence: 99%
“…The ligand‐receptor pair of the chemokine CX 3 CL1 (fractalkine) and CX 3 CR1 (fractalkine receptor), which is highly expressed by microglia appears to negatively affect M2 polarization of microglia . However, in view of the recently unveiled microglia heterogeneity, it seems probable that a system with two or few polarization states oversimplifies the multitude of microenvironmental niches and activation states in the CNS …”
Section: Introductionmentioning
confidence: 99%